CHANGES IMPLEMENTED IN THE SYSTEM OF SECONDARY SPECIAL AND PROFESSIONAL EDUCATION IN THE REPUBLIC OF UZBEKISTAN (AS AN EXAMPLE OF THE ACTION STRATEGY 2017-2021) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This article analyzes the reforms implemented in the system of secondary special and professional education in 2017-2021. In particular, the normative and legal documents adopted in the field and their content, the development of international cooperation relations and statistical analyzes related to the field are highlighted.